Inosine pranobex enhances human NK cell cytotoxicity by inducing metabolic activation and NKG2D ligand expression. Issue 1 (12th September 2019) - McCarthy, Michael T.; Lin, Da; Soga, Tomoyoshi; Adam, Julie; O'Callaghan, Christopher A.
Abstract: Inosine pranobex (IP) is a synthetic immunomodulating compound, indicated for use in the treatment of human papillomavirus‐associated warts and subacute sclerosing panencephalitis. Previous studies demonstrate that the immunomodulatory activity of IP is characterized by enhanced lymphocyte proliferation, cytokine production, and NK cell cytotoxicity. The activation of NKG2D signaling on NK cells, CD8 + T cells, and γδ T cells also produces these outcomes. We hypothesized that IP alters cellular immunity through the induction of NKG2D ligand expression on target cells, thereby enhancing immune cell activation through the NKG2D receptor. We tested this hypothesis and show that exposure of target cells to IP leads to increased expression of multiple NKG2D ligands. Using both targeted metabolic interventions and unbiased metabolomic studies, we found that IP causes an increase in intracellular concentration of purine nucleotides and tricarboxylic acid (TCA) cycle intermediates and NKG2D ligand induction. The degree of NKG2D ligand induction was functionally significant, leading to increased NKG2D‐dependent target cell immunogenicity. These findings demonstrate that the immunomodulatory properties of IP are due to metabolic activation with NKG2D ligand induction. Abstract : Cellular metabolic activation induces cell surface MICA expression by enhancing purine nucleotide synthesis. We show that inosine pranobex, a licensed antiviral drug, enhances purine nucleotide synthesis, NKG2D ligand expression, and cellular susceptibility to NKG2D‐dependent NK cell cytotoxicity in metabolically active cells.